Forging a Powerful Indo-India Bond: Reinventing the Eastern Connection in Foreign Policy - putra, Calvin Anthony; Anwar, Syaiful; Duarte, Editha Praditya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research extensively examines the intricate and multifaceted aspects of India's foreign policy, with a specific emphasis on its dynamic involvements in Southeast Asia, East Asia, and Indonesia. Against the backdrop of India's abundant resources, diverse biodiversity, and rich cultural heritage, the study underscores the strategic broadening of India's participation across various dimensions—ranging from socio-economic initiatives to political collaborations and security endeavors—within this expansive and diverse region. The proclamation of the Act East Policy by Prime Minister Narendra Modi serves as a crucial element in this holistic approach. It embodies a strategic framework crafted to fortify India's relationships with countries in both East Asia and Southeast Asia. This policy reflects a deliberate and far-reaching strategy to enhance diplomatic, economic, and security ties, leveraging India's strengths against the intricate tapestry of opportunities and challenges present in the region. By delving into the various facets of India's diplomatic outreach, this study seeks to unravel the layers of complexity surrounding India's engagements in Southeast Asia, East Asia, and Indonesia. Its objective is to offer a nuanced understanding of the motivations, challenges, and outcomes associated with India's multifaceted foreign policy in this strategically significant and culturally diverse region.